2010
DOI: 10.1143/jjap.49.08jk01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Humidity Treatment Conditions on the Interfacial Adhesion Energy between the Electroless-Plated Ni and Polyimide

Abstract: The effect of temperature/humidity treatment conditions on the interfacial adhesion energy between an electroless-plated Ni film and a polyimide substrate was evaluated by using a 180° peel test. The measured peel strength values decrease from 506.1 ±18.6 to 231.9 ±33.3 J/m2 due to the temperature/humidity treatment at 85 °C/85% relative humidity for 1000 h. X-ray photoelectron spectroscopy analysis of the peeled surfaces indicates that peeling occurs cohesively inside of the polyimide; this is related to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Therein, it is worth noting that the decrease prior to 12 h mostly occurred at the first 6 h because the rate of descending of the first 6 h is faster than the following rate from 6 h to 12 h. Afterward, in the second stage from 12 h to 18 h, there existed slight recovery from 2.54 ± 0.02 to 2.64 ± 0.03 N/mm. In the last 6 h of 1 day, the adhesive strength maintained in a steady state and continued to 72 h. In comparison, as inserted in Figure , the red dash line representing the adhesive strength of polyimide/Ni treated at 85 °C/85% RH is similar to the black curve of PP/Ni in the present study. However, it is obvious that the red dash line is only made up of two processes except the recovery.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Therein, it is worth noting that the decrease prior to 12 h mostly occurred at the first 6 h because the rate of descending of the first 6 h is faster than the following rate from 6 h to 12 h. Afterward, in the second stage from 12 h to 18 h, there existed slight recovery from 2.54 ± 0.02 to 2.64 ± 0.03 N/mm. In the last 6 h of 1 day, the adhesive strength maintained in a steady state and continued to 72 h. In comparison, as inserted in Figure , the red dash line representing the adhesive strength of polyimide/Ni treated at 85 °C/85% RH is similar to the black curve of PP/Ni in the present study. However, it is obvious that the red dash line is only made up of two processes except the recovery.…”
Section: Resultssupporting
confidence: 82%
“…Variation of adhesive strength of immersion in prepared sample solution ( V DMC / V EC = 1/1, C LiPF6 = 1 mol/L) as a function of time (the inserted red dash line presenting the adhesive strength of polyimide/Ni treated at 85 °C/85% RH ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These surface cracks are assumed to be closely tied to the interfacial adhesion. 19,20) XPS scans were performed on both sides of the delaminated surface after the four-point bending test to establish the fracture path. I shows the relative atomic concentrations on the upper and lower sides of the wafer as determined by XPS.…”
Section: Resultsmentioning
confidence: 99%
“…the 20 minute NaOH treatment sample. Using a 180° peel test, Park et al found that a nickel plated polyimide film had a much higher value of 0.51 ± 0.01 N/mm [11]. The differences can be attributed to the methodologies used in pre-treating the membrane, electroless plating, and peel test preparation.…”
Section: Peel Testsmentioning
confidence: 99%